HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PASIEN PREOPERASI SECTIO CAESAREA DI RUMAH SAKIT MA SENTOT PATROL INDRAMAYU - Kayubi Kayubi; Hasim Asyari; Indra Ruswadi (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2021)
Patients who are going for sectio caesarea, face uncomfortable feelings including anxiety, this is related to concerns about the threat to their lives, therefore, family support is very important to reduce anxiety, because it can increase the spirit of life and reduce patient anxiety and strengthen commitment to undergoing treatment. The purpose of the study was to understand the relationship between family support and anxiety levels of preoperative sectio caesarea patients at the MA Sentot Patrol Hospital, Indramayu. This study uses a quantitative research design with non-experimental methods and a descriptive approach. The population in this study were all patients who underwent sectio caesarea surgery as many as 42 patients and the sample used a total sampling technique, where the entire population was taken as a sample. The results of the study: 59.5% of families supported preoperative sectio caesarea patients, 31% of preoperative sectio caesarea patients experienced mild anxiety and 23.8% experienced severe anxiety, based on the chi square statistical test obtained p value 0.000 < (0.05) . Conclusion: there is a relationship between family support and anxiety levels of preoperative sectio caesarea patients at the MA Sentot Patrol Hospital, Indramayu Regency. Suggestion: for nurses, considering that there is a relationship between family support and the patient's level of anxiety, they should provide nursing interventions, especially for preoperative sectio caesarea patients, involving the family, so that the impact of the patient is calm in facing the sectio caesarea operation.